Date Seeds Steeping (Phoenix Dactylifera) Strengthen Sperm Cells Membrane and Reduce Malondialdehyde Level - Saryono Saryono; Retnani H.; Santoso D. (Jurnal Ners, 2015)
Introduction: Infertility in men is becoming more frequent and are usually caused by high levels of free radicals as a result of diet, smoking or pollution. Oxidative stress can be reduced by antioxidants, but a source of exogenous antioxidants are generally expensive. Date seed known contain a lot of antioxidants. The purpose of this study was to determine the effect of date seed steeping against MDA levels and sperm counts in rats model induced of monosodium glutamate (MSG). Method: This study was a pure experimental method using a post-test only with control group design. The treatments were grouped into 4 groups. Deglet Noor of date seed were used, washed and dried before roasting and smoothed. Sperm count is calculated in accordance research of Rahmanisa and Maisuri, (2013) and MDA examination with the C-18 method of TBARS (Thiobarbituric Acid Reactive Substances). Data were analyzed by one way ANOVA and continued with post hoc test. Results: There were differences in MDA levels and sperm counts between various groups. Giving date seed steeping 10.5 mg/gBW can decrease malondialdehyde levels in experimental animals after MSG induced significantly. The number of sperm increased significantly after the experimental animals were given a dose of date seed steeping 10.5 mg / g. Discussion: